Growth of dip coated magnesium oxide nanoflower thin films. (2nd January 2016) - Das, P. S.; Dey, A.; Mandal, A. K.; Dey, N.; Mukhopadhyay, A. K.
Abstract : The present work reports the synthesis of dip coated MgO nanoflower thin films. The films are developed without employing any capping agent and catalyst. A simple chemical deposition technique is adopted for this purpose. The MgO nanoflower thin films are characterised by X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, high resolution transmission electron microscopy and the related energy dispersive X-ray spectroscopy techniques. The results establish the phase purity and microstructural details of the MgO nanoflower thin films. These results are explained in terms of a proposed mechanism that suggests the growth process for the MgO nanoflower structures.